2012
DOI: 10.1111/j.1365-2214.2012.01371.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of family‐centred care: translation, adaptation and validation of the Measure of Processes of Care (MPOC‐56 and ‐20) for use in Japan

Abstract: The Japanese version of the MPOC has good psychometric properties and can be recommended for evaluation of the processes of child rehabilitation in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 19 publications
2
22
2
Order By: Relevance
“…The results support the validity and reliability of the Korean MPOC. Descriptive statistics demonstrated that the patterns of higher and lower scale scores are comparable with those of the Canadian (S. King, King, & Rosenbaum, ; S. King, Rosenbaum, & King, ), Dutch (Siebes et al, ; van Schie et al, ), Japanese (Himuro et al, ), and Swedish studies (Bjerre et al, ). Respectful and Supportive Care ranked the highest followed by Enabling and Partnership and Coordinated and Comprehensive Care.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The results support the validity and reliability of the Korean MPOC. Descriptive statistics demonstrated that the patterns of higher and lower scale scores are comparable with those of the Canadian (S. King, King, & Rosenbaum, ; S. King, Rosenbaum, & King, ), Dutch (Siebes et al, ; van Schie et al, ), Japanese (Himuro et al, ), and Swedish studies (Bjerre et al, ). Respectful and Supportive Care ranked the highest followed by Enabling and Partnership and Coordinated and Comprehensive Care.…”
Section: Discussionmentioning
confidence: 71%
“…The MPOC was originally developed in Canada with English‐speaking parents. The MPOC has been translated and evaluated for use in many countries including China (Wang, Petrini, & Guan, ), Japan (Himuro, Kozuka, & Mori, ), the Netherlands (van Schie, Siebes, Ketelaar, & Vermeer, ), Norway (Hagen & Bjorbækmo, ), Slovenia (Sršen, Vidmar, & Zupan, ), and Sweden (Bjerre et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…10 The MPOC-56 and MPOC-20 have been translated into Japanese and a study conducted to assess the psychometric properties when used with the families of children with disabilities. 11 This study demonstrated good internal consistency and test-retest reliability as well as good evidence of construct and concurrent validity. As family-centered care is a model for collaborative relationships between families and service providers, an additional version, the MPOC-SP, was developed for service providers.…”
Section: Introductionmentioning
confidence: 61%
“…The psychometric properties of the MPOC‐20 are similar to those of the original MPOC‐56 in terms of internal consistency, test–retest reliability, and construct validity . The MPOC‐56 and MPOC‐20 have been translated into Japanese and used to assess psychometric properties of psychological factors for families of children with disabilities . Himuro et al .…”
Section: Methodsmentioning
confidence: 93%
“…Himuro et al . demonstrated good internal consistency and test–retest reliability as well as good evidence of construct and concurrent validity …”
Section: Methodsmentioning
confidence: 98%